Plywood‐like structures of injection‐molded polypropylene. Issue 9 (13th July 2021) - Wang, Guanglong; Cao, Junhui; Hou, Shusen; Ding, Peng; Yu, Weixin; Yang, Zhijun; Chen, Jingbo
Abstract: N, N′‐dicyclohexyl‐2, 6‐naphthalenedicarboxamide, a commercial nucleating agent, can dissolve into molten polypropylene (PP) and self‐organize into needle‐like crystals when the melt temperature reaches 260°C. As temperature decreases, PP molecules crystallize on the surface of the needle‐like crystals with their c‐axis perpendicular to the long axis of the crystal. Under a flow field in injection molding, PP chains are parallel or perpendicular to the flow direction at different depths owing to the difference in crystallization kinetics and applied shear rate in the melt, forming a plywood‐like material. This unique structure can simultaneously improve the toughness and strength of plastic parts. Herein, we present a novel method of producing high‐performance plastic articles based on general plastics by manipulating their morphology and structure. Abstract : PP with nucleating agent was molded by conventional injection molding (CIM) or sequential co‐injection molding (SCIM). Under a flow field in injection molding, PP chains are parallel or perpendicular to the flow direction at different depths owing to the difference in crystallization kinetics and applied shear rate in the melt, forming a plywood‐like material. This unique structure can simultaneously improve the toughness and strength of plastic parts.